The effect of entrepreneurship education on career readiness as a job creator with self-efficacy as a mediating variable - Lubis, Arina Luthfini; Rais, Syafruddin; Rini, Rosie Oktavia Puspita; Friadi, John (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine the influence of entrepreneurship education on students’ career readiness as job creators, with self-efficacy serving as a mediating variable. The research is driven by the growing emphasis on preparing vocational graduates not only to become job seekers but also to develop as future entrepreneurs. Methodology: The study was conducted at Batam Tourism Polytechnic and involved 142 active students who had completed entrepreneurship courses. A quantitative approach was applied using a questionnaire consisting of 18 items representing three key constructs. Data were analyzed using SmartPLS 4.0 with the SEM-PLS method to assess both the measurement and structural models. Results: The results indicate that entrepreneurship education has a significant impact on career readiness, both directly (? = 0.42, p < 0.001) and indirectly through self-efficacy (indirect ? = 0.19, p < 0.001). Self-efficacy plays a significant mediating role in the relationship between entrepreneurship education and career readiness. The R² value of 0.51 suggests that the model explains more than half of the variance in the career readiness variable, and the model fit is considered good (SRMR = 0.071). Conclusions: Entrepreneurship education meaningfully enhances students’ confidence and their perceived readiness to become entrepreneurs, especially when supported by high levels of self-efficacy. Limitations: This study focuses only on cognitive and psychological aspects of readiness and does not account for practical challenges such as access to capital or other external barriers. Contribution: This study contributes to the fields of vocational entrepreneurship education, human resource management, and career development by providing insights into how educational programs can nurture entrepreneurial potential and promote proactive career planning among future graduates.